Incarcerated Pelvic Floor Peritoneal Hernia After Abdominoperineal Resection (APR): How To Prevent? - Prakosa, Yovan Indra Bayu; Setyawan, Nurcahya; Yushinta, Milleninda Pasca (http://dharmais.co.id/, 2025)
Introduction: Colorectal cancer is the third most common cancer worldwide. One of the procedures that is often performed in cases of distal rectal cancer is abdominoperineal resection (APR) procedure that leaves the pelvic cavity with an empty space. This condition increases the possibility of pelvic floor peritoneal hernia. We present a rare case of this condition and provide information regarding prevention and treatment.Case Presentation: A male, 74 years old, with recurrent constipation following APR, was retrospectively analyzed. Abdominal CT scan 6 months after surgery showed no residual tumor. On final arrival, he came with typical signs of total small bowel obstruction. Abdominal x-ray results showed signs of small bowel obstruction. The results of the operation found an incarcerated pelvic floor peritoneal hernia. The surgical procedures performed were entrapment release and hernia repair with a peritoneal flap. Complaint of obstruction sign improved two days postoperatively.Conclusion: Pelvic floor peritoneal hernias should not be forgotten in patients who experience recurrent constipation in postoperative APR. Recurrent constipation is caused by a herniation of the small bowel in the hernia sac. Chronic constipation should be considered an abnormal cause of obstruction. Poor wound healing processes cause the neck of the hernia to narrow and cause an incarcerated hernia. Closure of the pelvic floor needs to be restored post-operatively